MINDFULNESS AND RESILIENCE AS PREDICTORS OF STRESS AMONG UNIVERSITY STUDENTS - Zahra, Sayyeda Taskeen; Riaz, Saima (Journal of Postgraduate Medical Institute, 2018)
Objective: To investigate the relationship of mindfulness and resilience as predictors of stress among university students. Methodology: Using a cross-sectional survey research design, a stratified random sample of 391(191 male and 200 female) university students from University of Gujrat, Pakistan, participated in current study. Mindfulness was measured through five facet mindfulness questionnaire short form. Resilience was measures by using Connor Davidson resilience scale. Perceived stress scale was used to measure stress level of the participants. Data were analyzed using SPSS version 20. Results: There was significant positive relationship between mindfulness and resilience (r =.24, p <.001); significant negative relationship between mindfulness and perceived stress (r =-.49, p <.001); and resilience and perceived stress (r =-.12, p <.05). Hierarchical multiple regression analysis revealed that demographics, mindfulness and resilience overall accounted for 26% variance on perceived stress. Conclusion: Mindfulness and resilience were statistically significant predictors of stress among university students. Gender and age were also significant predictors of stress.